Properties of mortar containing high volume palm oil biomass waste - Abdul Shukor Lim, Nor Hasanah (2015)
The utilization of waste materials which are abundant and cheap, especially from clean resources, has become more pressing than ever. This paper, discusses the utilization of the wastes in the form of palm oil fuel ash and oil palm kernel shell in the production of mortar mixes as a part of new and innovative materials in construction industry. The studies include the basic properties including the morphology of the composite with regards to variations in the mix design process. In order to get a better performance in terms of strength development, the ash used has gone through heat treatment and ground up to the size less than 2µm. High volume of 60%, 80% and 100% palm oil fuel ash was used as cement replacement. The incorporation of more than 80% of palm oil biomass waste as cement and sand replacement has produced mortar having an improved compressive strength than normal mortar. In addition, the density of the mortar with biomass waste was less than normal mortar. Overall results have revealed that the inclusion of high volume palm oil biomass waste can produce mortar mix with high strength, good performance and most importantly more sustainable.